Oxidants induce Escherichia coli MarR glutathionylation in the presence of glutathione - Tianqi Wang; Honglei Liu; Huaiwei Liu; Yongzhen Xia; Luying Xun (Redox Biology)
The results of protein thiols reacting with oxidants may be different in the presence or absence of glutathione (GSH). Upon exposure to oxidants, such as Cu2+ and polysulfide, the multiple drug resistant regulator MarR dimer in Escherichia coli is believed to form tetramers linked by disulfide bonds between its Cys80 thiols. We confirmed this observation in the absence of GSH; however, the MarR-Cys80 thiol was primarily glutathionylated in the presence of GSH after MarR was treated with various oxidants, including octasulfur (S8), Cu2+, H2O2, ClO−, and a NO donor. When using S8 as the oxidizing agent, we identified four pathways to induce MarR-Cys80 glutathionylation. Since E. coli contains high concentrations of GSH, MarR is likely glutathionylated instead of forming tetramers inside the cells. When E. coli was exposed to S8, cellular levels of protein glutathionylation were increased and most MarR was glutathionylated, as shown by Western blot and LC-MS analyses. The glutathionylated MarR displayed reduced affinity to its cognate operator, resulting in the expression of its repressed genes. The results highlight the need to consider the wide presence of GSH when investigating protein thiol modification.